Adherence to antiretroviral therapy by adults living with HIV/aids: a cross-sectional study - Mariana de Morais Fortunato Miranda; Dayanne Rakelly de Oliveira; Glauberto da Silva Quirino; Célida Juliana de Oliveira; Maria Lúcia Duarte Pereira; Edilma Gomes Rocha Cavalcante (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To verify the association between adherence to antiretroviral treatment by adults with HIV/AIDS and sociodemographic factors, social and clinical support. Methods: Cross-sectional study, with a quantitative approach. Participation of 230 patients. Questionnaires of sociodemographic characterization, social and clinical support, and assessment of adherence to antiretroviral treatment were used. Descriptive and inferential statistics were performed. Results: Adherence was classified as good/adequate. An association with sex, income, employment, and level of education was noted. In social support: having access to health services; communication with health professionals; health education; having support to allow venting/talking about issues; information on HIV/AIDS; and company for leisure. In the clinical profile: non-interruption of the drug treatment due to absence from the service or due to changes in the medical prescription. Conclusion: Adherence was classified as good/adequate and especially associated with social support factors, which should be enhanced in clinical practice.